209k views
3 votes
What is the value of the expression (3a-b)/(6(b+a)) when a = 4 and b = -2? Show your work to support your answer.

please be specific

User Vertigo
by
4.5k points

1 Answer

4 votes

Answer:


1(1)/(6) or 1.166 Repeating

Explanation:

This is a very simple equation!

First you write it out


(3a-b)/(6(b+a))

Now you plug in your values.

a = 4

b= -2

So.


(3(4) - (-2))/(6(-2+4))

Now, follow PEMDAS

3 (4) = 12

12 - (-2) is the same as 12+2 Which equals 14

Now you have...


(14)/(6(-2+4))

-2 + 4 = 2

6 (2) = 12

Final Fraction is


(14)/(12)

Which can be reduced to


(7)/(6)

or

1.166 (repeating)

Hope this helps!

User Lannyboy
by
4.6k points